(untitled) (Academia Science Repository, 2023)
In this article, the questions of what is beauty, who is beautiful, analyze the understanding of the philosophical-aesthetic essence of "beauty". The problem of analyzing the expression of the concept of "beauty" in language (in English and Uzbek national cultures) has not been studied from the point of view of cognitive linguistics and linguistic culturology. The relevance of the article is determined by the study of the aesthetic landscape of the world in the English and Uzbek languages, the possibilities of expressing and reflecting the concept of "beauty" in the phraseological and lexical layers of the language, cultural characteristics and cognitive linguistics, linguoculturology, general linguistics.